Doppler and Duplex Sonography for the Diagnosis of the Irreversible Cessation of Brain Function (“Brain Death”): Current Guidelines in Germany and Neighboring Countries - Walter, U.; Schreiber, S. J.; Kaps, M. (Ultraschall in der Medizin - European Journal of Ultrasound, 2016)
Extra- and transcranial sonography of brain-supplying arteries is accepted worldwide in brain death protocols as a valid “ancillary” method of proving brain circulatory arrest. Color-coded duplex sonography and CT angiography have been newly incorporated in the fourth update of the German Medical Association’s guidelines for the determination of the irreversible cessation of brain function (“brain death”), effective July 2015. The updated guidelines address in more detail the diagnostic procedures and the required qualifications of the examiners. The present article summarizes the guidelines and the recommendations regarding the application and documentation of ultrasound findings for the diagnosis of brain circulatory arrest in children and adults, as valid in Germany. The method, limitations, and procedure in the case of inconclusive findings are described. Age-related minimum values of mean arterial pressure for the diagnosis of cerebral circulatory arrest in children are presented. A concise overview of the respective regulations for the use of sonography for diagnosing brain death in other countries, especially in the countries neighboring Germany, is given.